2001
DOI: 10.1038/sj.cdd.4400858
|View full text |Cite
|
Sign up to set email alerts
|

Pinocytic loading of cytochrome c into intact cells specifically induces caspase-dependent permeabilization of mitochondria: evidence for a cytochrome c feedback loop

Abstract: Previous studies introduced cytochrome c into intact cells via the disruptive techniques of microinjection or electroporation to provide support for the hypothesis that, in whole cells, cytochrome c release from mitochondria triggers caspase activation and other degradative changes. However, the types of measurements that could be undertaken with these techniques was limited. We used the simple and relatively gentle technique of pinocytic loading to demonstrate that, in intact cells, cytosolic cytochrome c spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Caspases or some cytosolic Human T-cell lymphoblastoid Jurkat yes [11][12][13] Human myelo-monocytic U-937 yes 13…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Caspases or some cytosolic Human T-cell lymphoblastoid Jurkat yes [11][12][13] Human myelo-monocytic U-937 yes 13…”
Section: Discussionmentioning
confidence: 99%
“…A statement that pinocytic loading of cytochrome c in cells is a "relatively gentle technique" as compared with "the disruptive techniques of microinjection or electroporation" 13 should be considered as a literary hyperbole (exaggeration), since this method is based on the enhancement of pinocytosis at the hyper-osmolar conditions followed by lysis (disruption) of intracellular vesicles, pinosomes, induced by hypo-osmolar shock. As for the viability of cells, here we report on an optimized electroporation procedure that results in a specific activation of apoptosis in up to 80% of cells after cytochrome c electroinjection and in a very low level of dead and apoptotic cells in control experiments.…”
Section: Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies (14) have shown that pinocytic loading of cytochrome c into the cells induced caspase activation and apoptosis. In agreement with this, we found that when macrophage cells were scraped-loaded with oxidized cytochrome c, this resulted in about 2-fold increase in caspase activity measured 2 h after the treatment (Fig.…”
Section: Reduction Of Cytochrome C Inhibits Caspase Activation Inmentioning
confidence: 99%